AB0224 Genetic Predictors of Response to TNF Alpha Inhibitors in Juvenile Idiopathic Arthritis. (9th June 2015) - Zajc Avramovič, M.; Dolžan, V.; Toplak, N.; Accetto, M.; Lusa, L.; Avcin, T.
Abstract : Background: Tumor necrosis factor α (TNF α) inhibitors are efficient drugs in treating patients with juvenile idiopathic arthritis (JIA), refractory to treatment with methotrexate. Nevertheless, a proportion of patients does not reach and sustain remission. Single nucleotide polymorphisms (SNP) in the promotor of TNF α and in the gene of TNF receptor-associated factor 1 (TRAF1) have been previously reported to be associated with response to treatment with biologics in adults patients with rheumatoid arthritis. Objectives: To investigate the effect of single nucleotide polymorphisms in the promotor gene for TNF α and in the genes for TRAF on response to therapy with TNF α inhibitors in JIA. Methods: The data of 61 consecutive patients with JIA treated with TNF α inhibitors at the University Children's Hospital Ljubljana from June 2011 to January 2015 were retrospectively reviewed. The disease activity was measured by JADAS 71 score 6 months after the beginning of treatment with TNF α blocker. Genotyping of SNPs in the genes for TNF α was performed using real time PCR methods. The following SNPs were analyzed: TNF A308G, TRAF 1b rs 3761847, TRAF 1a rs 10818488. Fisher exact test was used for statistical analysis. Results: The study group included 43 (70%) girls and 18 (30%) boys with JIA. Mean age at disease onset was 8.7 years. Seven (11%) patients had systemic arthritis, 19 (31%) polyarthritis (2 out of these were RF positive), 10 (15%) persistent oligoarthritis, 14 (22%) extended oligoarthritis, 7 (11%) juvenile psoriatic arthritis and 4 (7%) patients suffered from enthesitis related arthritis. Median disease duration until TNF α blockers were introduced was 18 months. Patients received 3 different TNF α blockers, 24 (39%) patients received infliximab, 22 (36%) etanercept and 15 (25%) adalimumab, respectively. Mean follow up time was 80 months. Six months after treatment was introduced 33 (54%) patients had inactive disease. Mean time to inactive disease was 6.9 months. Eight (13%) patients received two and 3 (5%) patients received three different TNF α blockers in the follow up period. Fifty one (84%) patients had at least one polymorphic allele in TRAF 1a rs 10818488 and 42 (69%) had at least one polymorphic allele in TRAF 1b rs 3761847. Using Fisher exact test no statistically significant relationship was found between the analyzed SNPs and inactive disease after 6 months of treatment. Conclusions: The analyzed SNPs in the promotor gene for TNF α and in the TRAF genes do not seem to significantly affect response to TNF α inhibitors in JIA. TRAF 1a rs 10818488 and TRAF 1b rs 3761847 might be associated with increased disease susceptibility as the incidence of polymorphic alleles was high in the population studied. Disclosure of Interest: None declared